A Systematic Review of Evidence for a Role of Rest-Activity Rhythms in Dementia - Smagula, Stephen F.; Gujral, Swathi; Capps, Chandler S.; Krafty, Robert T. (Frontiers in Psychiatry, 2019)
Background: Rest-activity rhythm (RAR) disruption may be a risk factor for dementia that can be objectively measured via wearable accelerometer-based technology. Therefore, it is possible that risk monitoring and preventive interventions could be developed targeting RARs. To evaluate whether current evidence supports these applications, we systematically reviewed current evidence linking RARs with dementia, its course, and mechanisms. Methods: Entering pre-defined search terms in PsycINFO, MEDLINE, and PubMed databases returned 192 unique titles. We identified 32 articles that met our primary inclusion criteria, namely, that they examined objective RAR measures in the context of dementia, cognition, or brain biomarkers. Results: Studies consistently found that people with dementia had less stable (5/6 studies), more fragmented (4/6 studies), lower amplitude rhythms (5/5 studies), that had a worse fit to 24-hour models (3/3 studies). Results from studies relating RARs to cognitive test performance (rather than diagnostic status) were more nuanced. RAR fragmentation was related to neurodegeneration biomarkers in 2/2 studies reporting; and 1/1 study found 24-hour model fit related to hippocampal hyperactivation. Although 2/2 studies found RARs related to markers of cerebrovascular disease, the specific RARs and cerebrovascular disease variables were not consistent. Longitudinal studies (3/3 articles) reported that lower amplitude and worse 24-hour rhythm fit predicted future cognitive impairment and executive function. Existing interventions aimed at modifying RARs have minimal effects (e.g., 0/4 studies demonstrated effects of morning light on 24-hour model fit; evening light did result in improved 24-hour fit in 2/2 studies reporting); these effects may be more evident in subgroups. Conclusions: Consistent evidence shows that dementia is associated with disrupted RARs. Importantly, a few recent studies have shown that RAR disruption is associated with dementia biomarkers and future cognitive impairment. Interventions (mostly focusing on using bright light) to modify RARs in people who already have dementia have generally had modest effects on RARs and have not modified dementia’s course. Given these findings, future studies are needed to understand how RARs relate to changes in brain health earlier in the disease process. A better understanding of the biopsychosocial mechanisms linking RARs with future dementia risk is needed to target intervention development.